STUDY OF HYDRODYNAMIC REGIMES IN INTERNAL PIPE PROFILES IN SHELL-AND-TUBE HEAT EXCHANGERS - Abdurasul Davronbekov; Muhammadbobir Khusanboev (European Science Publishing, 2023)
In the article, a new design of the inner pipe profile is recommended for shell-and-tube heat exchangers used in heat exchange processes in chemical industries. In the development of the structure, spherical concave and spherical linear pipe profiles were selected, and a systematic analysis of their operating parameters was carried out and intermediate limits were determined.
Keywords: flow mode, consumption, speed, model, visual state, systematic analysis, pipe, spherical tube, spherical tube, cooling agent.